1997
DOI: 10.1002/(sici)1097-4547(19970701)49:1<43::aid-jnr5>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of P2Y2 nucleotide receptors in human retinal pigment epithelial cells

Abstract: P2 nucleotide receptor expression in cultured human retinal pigment epithelial (RPE) cells was investigated using the photoaffinity ATP analog BzATP, polymerase chain reaction of reverse-transcribed RNA (RT-PCR) and fura-2 fluorescence measurement of changes in intracellular free calcium concentration ([Ca2+]i). In experiments carried out in RPE cells at passage 10-15, addition of micromolar concentrations of ATP, UTP, and ATPgammaS to RPE cells resulted in a rapid, transient 3.5-fold increase in [Ca2+]i follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 36 publications
(54 reference statements)
2
30
1
Order By: Relevance
“…It is a very weak partial agonist at P2Y 4 and P2Y 6 receptors (Chang et al 1995;Bogdanov et al 1998). Studies at likely endogenous P2X (P2X 2 : PC-12 cells, rat pelvic ganglion neurons; Michel et al 1996a;Zhong et al 1998) and P2Y receptors (P2Y 2 : retinal pigment epithelial cells, umbilical vein endothelial cells; Sullivan et al 1997;Conant et al 1998) conform with the pharmacology of ATPγS at recombinant receptors. Using human whole blood cells or bovine pulmonary artery endothelial cells, it has been demonstrated that ATPγS reversibly inhibits ecto-nucleotidases (pIC 50 =5.2; Beukers et al 1995;Chen and Lin 1997).…”
Section: Atpγ Smentioning
confidence: 87%
“…It is a very weak partial agonist at P2Y 4 and P2Y 6 receptors (Chang et al 1995;Bogdanov et al 1998). Studies at likely endogenous P2X (P2X 2 : PC-12 cells, rat pelvic ganglion neurons; Michel et al 1996a;Zhong et al 1998) and P2Y receptors (P2Y 2 : retinal pigment epithelial cells, umbilical vein endothelial cells; Sullivan et al 1997;Conant et al 1998) conform with the pharmacology of ATPγS at recombinant receptors. Using human whole blood cells or bovine pulmonary artery endothelial cells, it has been demonstrated that ATPγS reversibly inhibits ecto-nucleotidases (pIC 50 =5.2; Beukers et al 1995;Chen and Lin 1997).…”
Section: Atpγ Smentioning
confidence: 87%
“…Various stimuli have been shown to induce the release of intracellular Ca 2+ through the activation of inositol-1,4,5-trisphosphate receptors. These include growth factors [15], carbachol [34], histamine [35], and ATP which is speculated to be the "light-peak substance" [36,37]. Accordingly, Orai channels in RPE cells provide a way to refill intracellular Ca 2+ stores after activation of ryanodine or inositol-1,4,5-trisphosphate receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Some stimuli like mechanical stimulation, ATP, and bFGF have been shown to induce sustained Ca 2+ signals in RPE cells [16,36,38]. Other signals, including carbachol, lipophosphatidic acid, and stimulation with photoreceptor outer segments, lead to repetitive raises of the [Ca 2+ ] i [16,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…P2Y2 receptors have been identified in a wide variety of ocular cell types, particularly, in retina [26], retinal pigment epithelium [27][28][29], cornea [30,31], conjunctiva [32], lens [33], and ciliary epithelia [9,34]. P2Y2 receptor signaling and its function are apparent in the eye [35], and regulates multiple cellular functions in ocular physiology by calcium mobilization [9] including ion transport and fluid absorption [27,29], and mucin discharge [36].…”
Section: Discussionmentioning
confidence: 99%